UPDATE OF THE CONTENT OF PROFESSIONAL TRAINING OF FUTURE TEACHERS OF PHYSICAL EDUCATION ON THE BASIS OF AN INTEGRATIVE APPROACH (Psychology Travelogs, 2022)
The successful implementation of the modern school reform "New Ukrainian School" requires, first of all, high-quality personnel support. Along with the main principle of NUSH, which is that motivated teachers should work in school education, even more attention is focused on the quality of professional training of teachers - subjects, including physical education teachers. Thus, the current state of school education requires a competitive, creative, adaptive physical culture teacher who possesses modern pedagogical skills and abilities, capable of qualitatively and effectively carrying out the activities of a physical culture teacher in secondary education institutions. Summarizing the presented material, we note that updating the content of professional training of future physical culture teachers on the basis of an integrative approach plays a key role in the content of professional training of future physical culture teachers. Highlighting important topics and issues in the content of a number of disciplines, updating the content of disciplines, developing new courses create the necessary theoretical basis for the formation of a highly qualified professional physical education teacher.
Keywords: professional training; physical culture; personnel support; National University of Applied Sciences; teachers; students